Understanding the methodology and techniques to teach english for specific purposes in public technical high schools - Piedra Pérez, Wendy Vanessa (2021)
This paper describes that English for Specific Purposes (ESP) is a new tendency suggested by the Ministry of Public Education of Costa Rica for the curricular transformation in all the specialties that the system offers in the country. This transformation seeks, through a diverse, innovative, and creative learning environment, to endow students with the linguistic competencies to solve problems in the competitive and globalized environment with critical thinking. In addition, it contributes to the country's growing economy with qualified citizens that work in many companies that offer services in different areas. Understanding the methodology, the roles of teachers and students, and the techniques applied in ESP classrooms facilitate the language acquisitions and technical skills for each major.